Analisis Penerapan Sistem Akuntansi Pemerintahan Pada Dinas Perindustrian, Perdagangan Energi Dan Sumber Daya Mineral Provinsi Sumatera Utara - Elsa Putri; Kusmilawaty Kusmilawaty (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research aims to determine the implementation of the government accounting system in the department of industry, energy trade and mineral resources in North Sumatra province. This research uses a quantitative approach using primary and secondary data. Primary data was taken from interviews with 24 respondents who worked at the North Sumatra Province Office of Industry, Energy Trade and Mineral Resources, and secondary data was taken from financial reports. The sampling method used is convenience sampling. The research results show that the percentage obtained from calculating the answers is 84.10% of the answers stating "Yes". Meanwhile, 9.66% of interview answers stated "No" and 6.25% stated "Don't Know". This means that it can be concluded that the implementation of the government accounting system and the quality of regional financial reports at the Sumatra Province Office of Industry, Trade, Energy and Mineral Resources North is very good.